A survey of dedicated PASC clinics: Characteristics, barriers and spirit of collaboration. Issue 3 (21st February 2022) - Dundumalla, Shreya; Barshikar, Surendra; Niehaus, William N.; Ambrose, Anne F.; Kim, Soo Y.; Abramoff, Benjamin A.
Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection can produce prolonged multi‐organ system dysfunction and a worsened quality of life, a condition known as Post‐Acute Sequelae of SARS‐CoV‐2 Infection (PASC). In response, clinics have emerged dedicated to the treatment of individuals with PASC. Objective: To better understand the current characteristics of these clinics, the barriers they face, and the interest in collaboration between clinics. Design: A cross‐sectional survey study. Participants: Clinicians working within dedicated PASC centers (N = 94) identified primarily through the Survivor Corps database of Post‐COVID Care Centers. Additional clinics were found through news articles, an American Academy of Physical Medicine and Rehabilitation Database, and word of mouth. Methods: The branching logic electronic survey consisting of up to 39 questions was sent electronically to potential participants. Results: Complete survey responses were obtained from 45 clinics. There was a wide variety of different clinical models and specialties involved. The majority of clinics were homed in physical medicine and rehabilitation (40%), pulmonology (22%), and internal medicine (16%). Most clinics (73%) reported experiencing obstacles in the treatment of their patients, the most common of which included needing more established protocols (45%) and more clinical resources (24%). Most clinics (76%) also reported an interest in participating in a collaborative clinical network. Conclusion: Despite wide variability in current clinical models of PASC clinics, there are common practices such as using telemedicine, having initial visits longer than 30 minutes, involving certain specialties in the treatment team, and having the ability for follow‐up. Clinicians involved with PASC clinics have a strong interest in collaboration to improve patient care and overcome clinical obstacles, the most common of which is the lack of clear treatment protocols. More research is needed to identify which clinical models lead to better patient outcomes.